Raising student bilingualism through foreign language (English) teacher professional involvement - Kawałek , Alicja; Polok, Krzysztof; Przybysz- Zaremba, Małgorzata (Kultura-Społeczeństwo-Edukacja, 2022)
The bilingual process is widely observed among many people and many cultures. Out of the many different forms of bilingualism, the form of bilingualism that most often appears is the subsequent one, being the result of learning a second language in school settings. When developing this type of bilingualism, both the language competences of language teachers and the quality of their teaching talent are very important. In order to assess this type of interdependence, a study that focuses on the teachers’ skills and competences, on the one hand, and the impact L2 teachers have on students, on the other hand, was designed. The study involved 50 teachers and 100 students taught by them, all of them attending vocational secondary schools in southern Poland. All participants of the study (i.e. both the teachers and the students) were to answer six verification questions included in the Matura exam 2018. The results obtained during the research indicate the existence of an interdependence between the actual level of proficiency of foreign language (FL) teachers and the final evel of L2 proficiency presented by their students. Generally, the students led by language teachers with a higher overall level of communicative competence showed an overall better command of English in the survey.